DYNAMIC MORPHOLOGICAL CHANGES OF SPIT IN APRIL–MAY 2014 IN OPAK RIVER MOUTH, BANTUL, DAERAH ISTIMEWA YOGYAKARTA - Yan Restu Freski; Agung Setianto; Srijono Srijono (Geological Engineering Department Universitas Gadjah Mada, 2015)
As an oceanic coast, the beaches in the southern part of Java Island are predominantly influenced by ocean energy which is driven by periodical monsoon. This periodical process impacts the dynamic changes of spit in the river mouth system. Therefore, spit is a key to study the process in the southern coast of Java Island especially in Opak River Mouth. It needs a deep-root explanation about the morphological changes and the sedimentological mechanism. This research project was built by data such as spit geometry, aerial photographs and spontaneous wind direction. The supporting data included multitemporal IKONOS-Quickbird images from Google Earth and aerial photographs. These data were collected from field-work investigation and laboratorywork. The spit geometry was compiled by Global Positioning System handheld tracking along the edge of spit and crosschecked by aerial photograph using pole. The ultimate interpretation and periodic models were built by data reconstruction based on the geometry of spit and spontaneous wind direction. Spit changed weekly due to monsoon transition in April to May 2014. The morphological changes could be noted as the spit starting to be cut off by the highrate flow of Opak River. The process continued until the net drift moving westward. Keywords: April, coast, May, Opak river mouth, spit.